A preparation method for composite filter material for incineration tail gas purification
By preparing composite filter materials with multi-layer structure, the problem of aging and deformation of fiber materials in high temperature and high humidity environments is solved, and the effect of improving the efficiency of incineration exhaust gas and extending the service life of the filter materials is achieved.
Patent Information
- Application Number
- CN202510192996.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-21
AI Technical Summary
In the existing incineration exhaust gas treatment, the fiber material composite filter material aging and deforming under high temperature environments, resulting in a decrease in filtration efficiency and shortening of service life. In addition, the high humidity environment can easily lead to hygroscopic expansion of the filter material, affecting its performance, and may cause secondary pollution.
A composite filter material preparation method is adopted, including the preparation of a copolymer core layer and the impregnation of silicate gel, to form an intermediate shell layer, and an outer coating is formed by spraying the polytetrafluoroethylene dispersion, and a multi-layer structural filter material is formed after sintering.
It improves the mechanical strength and filtration performance of the filter material, enhances the interception ability of fine particles and corrosive gases, extends the service life of the filter material, reduces maintenance costs, and maintains stable performance in high temperature and high humidity environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tail gas treatment, and in particular to a method for preparing a composite filter material for purifying incineration tail gas. Background Art
[0002] Incineration tail gas treatment is one of the main ways to treat domestic waste. The tail gas generated during the incineration process contains a large amount of pollutants, such as particulate matter (smoke), acidic gases (such as HF, HCl, SOX, NOX, etc.), heavy metals (such as Hg, Pb, Cd, Cr, etc.), organic compounds and highly toxic organic pollutants (such as dioxins), etc., which pose a serious threat to the environment and human health. In order to effectively control the emission of pollutants in the incineration tail gas, bag dust collectors are widely used. Bag dust collectors have stable operation, convenient operation, high dust removal efficiency, and strong adaptability. The core component is the filter material. Bag dust removal technology filters out particulate matter in the tail gas through bags made of high-temperature and corrosion-resistant fiber materials; electrostatic dust removal technology uses an electric field to charge the particulate matter in the tail gas, and then adsorbs the charged particles to the dust collecting electrode under the action of the electric field, thereby effectively removing tiny particles. For acid gases in exhaust gas, wet desulfurization and denitrification technology is a commonly used method. Alkaline absorbents react chemically with acid gases to generate harmless salts that are discharged with wastewater. Dry / semi-dry desulfurization and denitrification technology uses solid adsorbents or slurry absorbents to absorb acid gases in exhaust gas. It has the advantages of simple equipment and small footprint.
[0003] The invention patent with the patent publication number CN112044175A discloses a composite catalytic filter material for low-temperature degradation of dioxins and its preparation method. The method uses a high-temperature resistant filter material as a catalyst carrier, and obtains a composite catalytic filter material of a three-way catalyst through the steps of filter material activation, in-situ precipitation, impregnation of V active components and low-temperature plasma oxidation. The composite catalytic filter material has excellent low-temperature activity and selectivity for catalytic degradation of dioxins, and improves catalytic activity and resistance to chlorine poisoning. The invention patent with the patent publication number CN110180272A discloses a filter material for waste incineration plant tail gas treatment, including a filter material bin, which is composed of an asbestos fiber layer, an aramid cloth layer, a glass fiber cloth layer, etc., and can improve the filtering effect.
[0004] However, in the prior art, incineration exhaust often contains high-temperature gases, and some fiber material composite filter materials are prone to aging and deformation in high-temperature environments. They will lose their original elasticity and strength at high temperatures, making the filter material structure loose and unable to effectively intercept pollutants, resulting in a decrease in filtration efficiency and a shortened service life of the filter material. In addition, a high humidity environment can easily cause the filter material to absorb moisture and expand, reducing its air permeability and filtration efficiency. In particular, for fiber materials with strong hygroscopicity such as asbestos fiber layers, high humidity will make them soft and easy to deform, thereby affecting the overall performance of the filter material, and may also cause the growth of microorganisms inside the filter material, leading to secondary pollution. At the same time, incineration exhaust gas usually contains a large number of fine particles, such as PM2.5, PM10, etc. These fine particles have high requirements for the filtration efficiency of the filter material, and some composite filter materials cannot effectively intercept fine particles due to their large diameter or unreasonable pore structure, resulting in a decrease in filtration efficiency. Incineration exhaust gas also contains some sticky substances, such as tar, grease, etc., which are easy to adhere to the surface of the filter material to form filter cake, block the pores of the filter material, reduce its air permeability and filtration efficiency, increase replacement frequency and operation and maintenance costs, and affect the continuity and stability of incineration exhaust gas treatment. Summary of the invention
[0005] In order to solve the problems mentioned in the above background technology, the present invention provides a method for preparing a composite filter material for purifying incineration tail gas.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0008] S1. Add tetraethyl orthosilicate, hydrochloric acid, water and ethanol into a mixer and mix them evenly. Under stirring, control the heating temperature of the solution and stir for 2-3 hours to obtain a silicate gel. Immerse the copolymer core layer in the silicate gel for impregnation, and let it stand at room temperature for 24 hours to obtain an intermediate shell layer.
[0009] S2. Add polytetrafluoroethylene resin, ammonium perfluorooctanoate and water into a mixer and mix them evenly. Disperse them through a high-speed stirrer for 20-30 minutes to obtain a polytetrafluoroethylene dispersion. Spray the polytetrafluoroethylene dispersion evenly on the surface of the intermediate shell layer. The spraying pressure is 0.3-0.5MPa. The distance between the spray gun and the intermediate shell layer is 15-20cm. Move the spray gun at a speed of 3-5cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24 hours, and place it in a high-temperature furnace for sintering for 2-3 hours to obtain a composite filter material for purifying incineration exhaust gas.
[0010] Furthermore, the copolymer core layer in step S1 is prepared by the following steps:
[0011] Under nitrogen protection, add isohexene to a reactor pre-filled with tetrahydrofuran, add ethyl diazoacetate and copper acetate, stir evenly, add benzoyl peroxide dropwise to the solution, heat in an oil bath, react for 1-2 hours under stirring, increase the temperature, continue to react with stirring for 3-5 hours, after the reaction is completed, pour into methanol to precipitate, filter, wash three times with methanol, and dry in a vacuum drying oven at 60°C to constant weight to obtain a copolymer core layer.
[0012] Furthermore, in step S1, the mass ratio of tetraethyl orthosilicate, hydrochloric acid, water and ethanol is (1-1.2):(5-6):(2-2.5):(2-2.5), and the mass ratio of silicate gel and copolymer core is (4-5):(1.5-1.8).
[0013] Furthermore, in step S1, the heating temperature is controlled to be 40-50° C. and the stirring speed is controlled to be 50-100 rpm.
[0014] Furthermore, in step S2, the mass ratio of polytetrafluoroethylene resin, ammonium perfluorooctanoate and water is (20-25): (1-1.2): 400, and the mass ratio of polytetrafluoroethylene dispersion and intermediate shell layer is (1-1.5): (3-4).
[0015] Furthermore, in step S2, the speed of the high-speed stirrer is 1000-1100 rpm, and the sintering temperature in the high-temperature furnace is 380-400°C.
[0016] Furthermore, the molar ratio of isohexene, tetrahydrofuran, ethyl diazoacetate, copper acetate and benzoyl peroxide is (2-3):10:(3-4):(0.07-0.08):(0.5-0.7).
[0017] Furthermore, the temperature of the oil bath heating is 60-65°C, the temperature is raised to 100-105°C, and the stirring speed is 100-200rpm.
[0018] Beneficial effects of the present invention:
[0019] 1. In the technical solution of the present invention, the copolymer core layer is formed by free radical polymerization of isohexene and ethyl diazoacetate in the presence of benzoyl peroxide as a free radical initiator and copper acetate as a catalyst to form a copolymer with a regular alternating sequence and a three-dimensional network structure. The dense polymer network in the copolymer core layer not only enhances the mechanical strength of the filter material, but also improves its filtration performance and stability. The pores and channel structures in the network give the core layer certain air permeability and filtration performance.
[0020] 2. In the technical solution of the present invention, the intermediate shell layer is formed by impregnating and curing the copolymer core layer with silicate gel, and is interconnected by polycondensation reaction. When the silicate gel penetrates into the pores and channels of the copolymer core layer, it interacts with the functional groups on the surface and inside of the core layer to form a strong bond. The cured silicate gel layer has a dense microstructure, which can effectively block fine particles and corrosive gases in the incineration exhaust gas, while enhancing the overall mechanical strength and stability of the filter material.
[0021] 3. In the technical solution of the present invention, the polytetrafluoroethylene coating is formed by uniformly coating the polytetrafluoroethylene dispersion on the surface of the intermediate shell layer by spraying, and then sintering. During the sintering process, the polytetrafluoroethylene particles melt and flow at high temperature to form a dense coating structure. The coating has extremely low surface energy, making it difficult for particulate matter and corrosive gases in the incineration exhaust gas to adhere to and diffuse on its surface. At the same time, the coating and the intermediate shell layer form a strong composite structure through physical or chemical bonding, which further enhances the overall performance of the filter material.
[0022] 4. In the technical solution of the present invention, the multi-layer structure of the composite filter material realizes multi-stage filtration of incineration exhaust gas, improves the efficiency and effect of exhaust gas treatment, reduces the content of harmful substances in emissions, extends the service life of the filter material, reduces the replacement frequency and maintenance cost, and enables the filter material to operate stably for a long time in the high temperature environment of incineration exhaust gas.
[0023] 5. In the technical solution of the present invention, the polytetrafluoroethylene coating has extremely low surface energy, which makes it difficult for particulate matter and sticky substances in the incineration exhaust gas to adhere to and diffuse on its surface. It is not easy to be contaminated during use and is easy to clean and maintain, which reduces the cleaning and maintenance costs and improves the operating efficiency of the equipment. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.
[0026] Preparation Example 1
[0027] The copolymer core layer comprises the following steps to prepare:
[0028] Under nitrogen protection, 200 g of isohexene was added to a reactor pre-loaded with 1000 g of tetrahydrofuran, 300 g of ethyl diazoacetate and 7 g of cupric acetate were added, and the mixture was stirred evenly at a speed of 100 rpm. 50 g of benzoyl peroxide was added dropwise to the solution, and the oil bath was heated to 60° C. After reacting for 1 h under stirring, the mixture was heated to 100° C. and continued to react at a speed of 100 rpm for 3-5 h. After the reaction was completed, the mixture was poured into methanol to precipitate, filtered, washed three times with methanol, and dried in a vacuum drying oven at 60° C. to constant weight to obtain a copolymer core layer.
[0029] Preparation Example 2
[0030] The copolymer core layer comprises the following steps to prepare:
[0031] Under nitrogen protection, 250g of isohexene was added to a reactor pre-loaded with 1000g of tetrahydrofuran, 350g of ethyl diazoacetate and 7-8g of cupric acetate were added, and the mixture was stirred evenly at a speed of 150rpm. 60g of benzoyl peroxide was added dropwise to the solution, and the oil bath was heated to 62°C. After reacting for 1.5h under stirring, the mixture was heated to 102°C and continued to react at a speed of 150rpm for 4h. After the reaction was completed, the mixture was poured into methanol to precipitate, filtered, washed three times with methanol, and dried to constant weight in a vacuum drying oven at 60°C to obtain a copolymer core layer.
[0032] Preparation Example 3
[0033] The copolymer core layer comprises the following steps to prepare:
[0034] Under nitrogen protection, 300 g of isohexene was added to a reactor pre-loaded with 1000 g of tetrahydrofuran, 400 g of ethyl diazoacetate and 7-8 g of cupric acetate were added, and the mixture was stirred evenly at a speed of 200 rpm. 70 g of benzoyl peroxide was added dropwise to the solution, and the oil bath was heated to 65° C. After reacting for 2 h under stirring, the mixture was heated to 105° C. and continued to react at a speed of 200 rpm for 5 h. After the reaction was completed, the mixture was poured into methanol to precipitate, filtered, washed three times with methanol, and dried in a vacuum drying oven at 60° C. to constant weight to obtain a copolymer core layer.
[0035] Example 1
[0036] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0037] S1. Add 100 g of tetraethyl orthosilicate, 500 g of hydrochloric acid (mass fraction of 10%), 200 g of water and 200 g of ethanol into a mixer and mix them evenly. Heat the solution to 40° C. and stir at 50 rpm for 2 h to obtain a silicate gel. Immerse 150 g of the copolymer core layer obtained in Preparation Example 1 into 400 g of the silicate gel and allow to stand at room temperature for 24 h to obtain an intermediate shell layer.
[0038] S2. Add 200g of polytetrafluoroethylene resin, 10g of ammonium perfluorooctanoate and 4000g of water into a mixer and mix them evenly. Disperse them at a speed of 1000rpm for 20min using a high-speed stirrer to obtain a polytetrafluoroethylene dispersion. Spray 100g of the polytetrafluoroethylene dispersion evenly on the surface of 300g of the intermediate shell layer. The spraying pressure is 0.3MPa. The distance between the spray gun and the intermediate shell layer is 15cm. Move the spray gun at a speed of 3cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24h, place it in a high-temperature furnace, and sinter it at a temperature of 380°C for 2h to obtain a composite filter material for purifying incineration exhaust gas.
[0039] Example 2
[0040] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0041] S1. Add 105 g of tetraethyl orthosilicate, 520 g of hydrochloric acid (mass fraction of 10%), 210 g of water and 205 g of ethanol into a mixer and mix them evenly. Heat the solution to 42° C. under stirring, and stir at a speed of 60 rpm for 2 h to obtain a silicate gel. Immerse 155 g of the copolymer core layer obtained in Preparation Example 2 into 410 g of the silicate gel for impregnation, and let stand at room temperature for 24 h to obtain an intermediate shell layer.
[0042] S2. Add 208g of polytetrafluoroethylene resin, 10.2g of ammonium perfluorooctanoate and 4000g of water into a mixer and mix them evenly. Disperse them at a speed of 1000rpm for 25min using a high-speed stirrer to obtain a polytetrafluoroethylene dispersion. Use a spraying method to evenly coat 110g of the polytetrafluoroethylene dispersion on the surface of the 310g intermediate shell layer. The spraying pressure is 0.3MPa. The distance between the spray gun and the intermediate shell layer is 16cm. Move the spray gun at a speed of 3cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24h, place it in a high-temperature furnace, and sinter it at a temperature of 385°C for 2h to obtain a composite filter material for purifying incineration exhaust gas.
[0043] Example 3
[0044] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0045] S1. Add 108 g of tetraethyl orthosilicate, 540 g of hydrochloric acid (mass fraction of 10%), 212 g of water and 224 g of ethanol into a mixer and mix them evenly. Heat the solution to 45° C. and stir at 70 rpm for 2.5 h to obtain a silicate gel. Immerse 162 g of the copolymer core layer obtained in Preparation Example 3 into 430 g of the silicate gel and allow to stand at room temperature for 24 h to obtain an intermediate shell layer.
[0046] S2. Add 225g of polytetrafluoroethylene resin, 10.5g of ammonium perfluorooctanoate and 4000g of water into a mixer and mix them evenly. Disperse them at a speed of 1000rpm for 25min using a high-speed stirrer to obtain a polytetrafluoroethylene dispersion. Spray 115g of the polytetrafluoroethylene dispersion evenly on the surface of the 330g intermediate shell layer. The spraying pressure is 0.4MPa. The distance between the spray gun and the intermediate shell layer is 18cm. Move the spray gun at a speed of 4cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24h, place it in a high-temperature furnace, and sinter it at a temperature of 390°C for 2.5h to obtain a composite filter material for purifying incineration exhaust gas.
[0047] Example 4
[0048] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0049] S1. Add 110 g of tetraethyl orthosilicate, 550 g of hydrochloric acid (mass fraction of 10%), 215 g of water and 230 g of ethanol into a mixer and mix them evenly. Heat the solution to 45° C. under stirring, and stir at a speed of 80 rpm for 2.5 h to obtain a silicate gel. Immerse 170 g of the copolymer core layer obtained in Preparation Example 1 into 480 g of the silicate gel for impregnation, and let stand at room temperature for 24 h to obtain an intermediate shell layer.
[0050] S2. Add 235g of polytetrafluoroethylene resin, 11g of ammonium perfluorooctanoate and 4000g of water into a mixer and mix them evenly. Disperse them at a speed of 1100rpm for 30min using a high-speed stirrer to obtain a polytetrafluoroethylene dispersion. Spray 135g of the polytetrafluoroethylene dispersion evenly on the surface of 375g of the intermediate shell layer. The spraying pressure is 0.5MPa. The distance between the spray gun and the intermediate shell layer is 20cm. Move the spray gun at a speed of 5cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24h, place it in a high-temperature furnace, and sinter it at a temperature of 390°C for 3h to obtain a composite filter material for purifying incineration exhaust gas.
[0051] Example 5
[0052] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0053] S1. Add 115 g of tetraethyl orthosilicate, 580 g of hydrochloric acid (mass fraction of 10%), 240 g of water and 240 g of ethanol into a mixer and mix them evenly. Heat the solution to 48° C. and stir at 100 rpm for 3 h to obtain a silicate gel. Immerse 170 g of the copolymer core layer obtained in Preparation Example 2 into 490 g of the silicate gel and let stand at room temperature for 24 h to obtain an intermediate shell layer.
[0054] S2. Add 240g of polytetrafluoroethylene resin, 11g of ammonium perfluorooctanoate and 4000g of water into a mixer and mix them evenly. Disperse them at a speed of 1100rpm for 30min using a high-speed stirrer to obtain a polytetrafluoroethylene dispersion. Spray 140g of the polytetrafluoroethylene dispersion evenly on the surface of the 390g intermediate shell layer. The spraying pressure is 0.5MPa. The distance between the spray gun and the intermediate shell layer is 20cm. Move the spray gun at a speed of 5cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24h, place it in a high-temperature furnace, and sinter it at a temperature of 400°C for 3h to obtain a composite filter material for purifying incineration exhaust gas.
[0055] Example 6
[0056] A method for preparing a composite filter material for purifying incineration tail gas comprises the following steps:
[0057] S1. Add 120 g of tetraethyl orthosilicate, 600 g of hydrochloric acid (mass fraction of 10%), 250 g of water and 250 g of ethanol into a mixer and mix them evenly. Heat the solution to 50° C. and stir at 100 rpm for 3 h to obtain a silicate gel. Immerse 180 g of the copolymer core layer obtained in Preparation Example 3 into 500 g of the silicate gel and let stand at room temperature for 24 h to obtain an intermediate shell layer.
[0058] S2. Add 250g of polytetrafluoroethylene resin, 12g of ammonium perfluorooctanoate and 4000g of water into a mixer and mix them evenly. Disperse them at a speed of 1100rpm for 30min using a high-speed stirrer to obtain a polytetrafluoroethylene dispersion. Use a spraying method to evenly coat 150g of the polytetrafluoroethylene dispersion on the surface of a 400g intermediate shell layer. The spraying pressure is 0.5MPa. The distance between the spray gun and the intermediate shell layer is 20cm. Move the spray gun at a speed of 5cm / s to evenly cover the surface of the intermediate shell layer with the coating. Let it stand at room temperature for 24h, place it in a high-temperature furnace, and sinter it at a temperature of 400°C for 3h to obtain a composite filter material for purifying incineration exhaust gas.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that ethyl diazoacetate is used to replace the copolymer core layer prepared in Preparation Example 1, and the remaining steps are the same as those in Example 1.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 2 is that isohexene is used to replace the copolymer core layer prepared in Preparation Example 2, and the remaining steps are the same as those in Example 2.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 3 is that the copolymer core layer prepared in Preparation Example 3 is not added, and the remaining steps are the same as Example 3.
[0065] Comparative Example 4
[0066] The difference between this comparative example and Example 4 is that silicate gel is not added, and the remaining steps are the same as those of Example 4.
[0067] Comparative Example 5
[0068] The difference between this comparative example and Example 5 is that no polytetrafluoroethylene dispersion is added, and the remaining steps are the same as those of Example 5.
[0069] 100 g of each composite filter material prepared in Examples 1-6 and Comparative Examples 1-5 were placed in 9 identical tail gas treatment devices, respectively. The tail gas treatment devices were set up in accordance with GB / T 29152-2012 "Equipment for treating tail gas from waste incineration".
[0070] Use standard gas and dilution gas to prepare a certain concentration of NOx (NO and NO 2 mixture, concentration of 500ppm), dust (carbon black particles, average particle size of 100μm, concentration of 0.5mg / m 3 ), dioxin analogs (trichlorobiphenyl, concentration 1ng TEQ / m 3 ), viscous substances (atomized diesel, concentration 0.1mg / m 3 ) was used, and the flow rate of the simulated exhaust gas was controlled to be 0.1 L / min. The simulated exhaust gas was introduced into each exhaust gas treatment device in batches, and the exhaust gas introduction time was 60 min.
[0071] Before and after exhaust gas treatment, the concentrations of NOx, dust and dioxin analogs in the exhaust gas are detected by gas analyzers. The detection accuracy of NOx is at least ±1ppm, and the detection accuracy of dust is at least ±0.1mg / m 3 The detection accuracy of dioxin analogues is at least ±0.01ng TEQ / m 3 , the detection accuracy of sticky substances is at least ±0.01mg / m 3 . Record the concentration values before and after treatment, and calculate the removal efficiency for each pollutant. Removal efficiency = (concentration before treatment - concentration after treatment) / concentration before treatment × 100%. The results are shown in Table 1:
[0072] Table 1. Tail gas removal efficiency results of Examples 1-6 and Comparative Examples 1-5
[0073]
[0074] As shown in Table 1, the composite filter materials of Examples 1-6 have high removal efficiencies of NOx, dust, dioxin analogs and viscous substances, while the removal efficiencies of Comparative Examples 1-5 are relatively low. Examples 1-6 all use the copolymer core layer prepared in Preparation Examples 1-3, which may provide good mechanical strength and chemical stability, and its specific chemical structure may help to adsorb and decompose certain pollutants. Comparative Example 1 replaces the copolymer core layer with ethyl diazoacetate, Comparative Example 2 replaces it with isohexene, and Comparative Example 3 does not add the copolymer core layer at all, resulting in a significant reduction in the removal efficiency of NOx, dust, dioxin analogs and viscous substances, indicating that the copolymer core layer plays a key role in the performance of the composite filter material.
[0075] Examples 1-6 all form an intermediate shell layer by impregnating silicate gel. The silicate gel may provide additional adsorption surface area and chemical stability, which helps to capture and fix pollutants. Comparative Example 4 does not add silicate gel, resulting in a decrease in the removal efficiency of all pollutants, but the decrease is not as significant as completely removing the copolymer core layer.
[0076] In Examples 1-6, the surface of the intermediate shell layer is coated with polytetrafluoroethylene dispersion to form an outer layer. Polytetrafluoroethylene has good chemical corrosion resistance and hydrophobicity, which may help prevent the accumulation and penetration of pollutants on the surface of the filter material. In Comparative Example 5, no polytetrafluoroethylene dispersion is added, resulting in a decrease in the removal efficiency of all pollutants.
[0077] In summary, the composite filter material with a multilayer structure in Examples 1-6 may improve the removal efficiency of the composite filter material for NOx, dust, dioxin analogs and sticky substances by providing mechanical strength, chemical stability, adsorption surface area and hydrophobicity.
[0078] In the description of the specification, the description with reference to the terms "preparation example", "embodiment", "various embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or preparation examples in a suitable manner.
[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a composite filter material for treating incineration tail gas, characterized in that: The following steps are involved: S1. Add tetraethyl orthosilicate, hydrochloric acid, water and ethanol into a mixer and mix them evenly. Under stirring, control the heating temperature and stir for 2-3 hours to obtain a silicate gel. Immerse the copolymer core layer in the silicate gel for impregnation, and let it stand at room temperature for 24 hours to obtain an intermediate shell layer. S2, adding polytetrafluoroethylene resin, ammonium perfluorooctanoate and water into a mixer and mixing them evenly, dispersing them through a high-speed stirrer for 20-30 minutes to obtain a polytetrafluoroethylene dispersion, coating the polytetrafluoroethylene dispersion evenly on the surface of the intermediate shell layer, standing at room temperature for 24 hours, and sintering them in a high-temperature furnace for 2-3 hours to obtain a composite filter material for incineration tail gas treatment; Wherein, the copolymer core layer in step S1 comprises the following steps to prepare: Under nitrogen protection, add isohexene into a reactor pre-filled with tetrahydrofuran, add ethyl diazoacetate and cupric acetate, stir evenly, add benzoyl peroxide dropwise, heat in an oil bath, react for 1-2 hours under stirring, increase the temperature, continue stirring and react for 3-5 hours, after the reaction is completed, precipitate, filter, wash, and dry to obtain a copolymer core layer.
2. The method for preparing a composite filter material for treating incineration exhaust gas according to claim 1, characterized in that: In step S1, the mass ratio of tetraethyl orthosilicate, hydrochloric acid, water and ethanol is (1-1.2):(5-6):(2-2.5):(2-2.5), and the mass ratio of silicate gel and copolymer core is (4-5):(1.5-1.8).
3. The method for preparing a composite filter material for treating incineration tail gas according to claim 1, characterized in that: In step S1, the heating temperature is controlled to be 40-50° C. and the stirring speed is controlled to be 50-100 rpm.
4. The method for preparing a composite filter material for treating incineration tail gas according to claim 1, characterized in that: In step S2, the mass ratio of polytetrafluoroethylene resin, ammonium perfluorooctanoate and water is (20-25): (1-1.2): 400, and the mass ratio of polytetrafluoroethylene dispersion and intermediate shell layer is (1-1.5): (3-4).
5. The method for preparing a composite filter material for treating incineration tail gas according to claim 1, characterized in that: In step S2, the speed of the high-speed stirrer is 1000-1100 rpm, and the sintering temperature in the high-temperature furnace is 380-400°C.
6. The method for preparing a composite filter material for treating incineration tail gas according to claim 1, characterized in that: The molar ratio of isohexene, tetrahydrofuran, ethyl diazoacetate, copper acetate and benzoyl peroxide is (2-3):10:(3-4):(0.07-0.08):(0.5-0.7).
7. The method for preparing a composite filter material for treating incineration tail gas according to claim 1, characterized in that: The temperature of the oil bath heating is 60-65°C, and the temperature is raised to 100-105°C, and the stirring speed is 100-200rpm.
Citation Information
Patent Citations
Filter material for tail gas treatment of waste incineration plant
CN110180272A
Composite catalytic filter material for degrading dioxin at low temperature and preparation method thereof
CN112044175A
A method for reducing the emission of organic products from incomplete combustion
CA2046281A1
Lyophobic and oleophylic micro nano-coatings applied to of oil filtering dehydration and preparation method thereof
CN101601940A